ANALISA KEUANGAN KELAYAKAN USAHA TERNAK AYAM KAMPUNG SUPER - Sitti Aminah Hamzah Karim; Arie Kurniawan; Wisra Mattalatta; Suci Rahmawati; Nuranisa Nuranisa; Syahbuddin Syahbuddin; Dwi Kartika; Sri Hartati (Asosiasi Dosen Muda Indonesia, 2022)
Research is an activity carried out systematically, planning and following scientific concepts to obtain something objective and rational about something. The type of research used in this research is case study research. In this study the researcher will analyze the feasibility study of super free-range chicken business. the problem is whether the super free-range chicken business is feasible or not to be made as a business, considering that the enlargement period for super free-range chickens is longer when compared to broiler chickens. The location of the research was carried out at Pak Gun's chicken farm in Malotong Village, Ampana Kota District, Tojo una-una Regency. Based on the results of our research and discussion that the super free-range chicken business in Malotong Village, Ampana District, City of Tojo Una-Una Regency is feasible to do, this can be seen in the super free-range chicken business that is feasible to be used as a business and is profitable because it has a higher R/C value. greater than 1, which is equal to 1.2, which can be assumed that free-range chicken farms make a profit. The total production costs include fixed costs and variable costs incurred in the super free-range chicken business of Rp. 2,848,000, - very efficient, so it can be assumed to be feasible. The revenue received is Rp. 15,785,000, - is the gain from the total production of 287 heads multiplied by the selling price per head of Rp. 55.000,-. with the amount of income earned Rp. 2,437,000,-